2009
DOI: 10.1111/j.1399-3046.2008.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐transplant lymphoproliferative disorder after pediatric liver transplantation: Characteristics and outcome

Abstract: The clinical presentations were protean and not specific. A high index of suspicion is important for early diagnosis as it correlates with more benign lesions and more favorable outcume. The lower mortality rate in our series is concordant with that reported in more recent articles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 15 publications
2
40
0
Order By: Relevance
“…In the present study, the mortality rate reached 25%. Fernandez et al have found a mortality rate of 18% in a similar population (11) . Finally, lymphomas are relatively uncommon and potentially fatal complications that may occur at any moment after liver transplant in children and that present variable clinical and imaging findings.…”
Section: Studies In Patients Submitted To Hepatic Transplantation Havmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, the mortality rate reached 25%. Fernandez et al have found a mortality rate of 18% in a similar population (11) . Finally, lymphomas are relatively uncommon and potentially fatal complications that may occur at any moment after liver transplant in children and that present variable clinical and imaging findings.…”
Section: Studies In Patients Submitted To Hepatic Transplantation Havmentioning
confidence: 99%
“…In the study developed by Fernandez et al, who have also evaluated Radiol Bras. 2012 Jan/Fev;45(1):7-11 children submitted to liver transplant, the mean time elapsed between the transplant and development of the disease was 25 months, ranging from seven to 47 months (11) . Age at the moment of the transplantation was the sole risk factor for development of lymphoma observed in the present study, which may be associated with previous contact of the patients with the Epstein-Barr virus (EBV).…”
Section: Studies In Patients Submitted To Hepatic Transplantation Havmentioning
confidence: 99%
See 2 more Smart Citations
“…Outcomes for children with PTLD are much better than for adults. (Dharnidharka, 2010) Outcomes are highest for recipients of renal and liver allografts, with survival rates for children reported at 89% and 80% respectively (Fernandez et al, 2009;McDonald et al, 2008), but significantly lower for other types of transplant, 67% at five years in heart transplant recipients, 54% and 42% at 3 and 5 years respectively in lung transplant recipients. Webber et al, 2006) Further, the overall survival according to stage is 80% for stages I/II, 61% for stage III, 20% for CNS involvement and less than 20% for BM involvement.…”
Section: Prognosismentioning
confidence: 99%